2003
DOI: 10.1016/s0029-7844(03)00067-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genital prolapse on assessment of bladder neck mobility by the Q-tip test

Abstract: Q-tip angles were significantly altered by vaginal prolapse and bladder fullness. With an empty bladder, the median Q-tip angle measured with the prolapse reduced was significantly less than that measured without reduction (53 degrees, interquartile range 25-65, versus 68 degrees, interquartile range 45-75; P <.001). With a full bladder, similar but lesser results were obtained (33 degrees, interquartile range 15-55 [reduced] versus 48 degrees, interquartile range 31-60 [unreduced]; P <.001). The median Q-tip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“… Q-tip angle: one study concluded that the Q-tip test is affected by POP. The angles were smaller with the prolapse reduced and with a full bladder [ 64 ]. A substantial correlation (r=0.68) between POP-Q point Aa and Q-tip angle was noted in a study on women presenting predominantly with SUI and anterior wall prolapse [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“… Q-tip angle: one study concluded that the Q-tip test is affected by POP. The angles were smaller with the prolapse reduced and with a full bladder [ 64 ]. A substantial correlation (r=0.68) between POP-Q point Aa and Q-tip angle was noted in a study on women presenting predominantly with SUI and anterior wall prolapse [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the diagnosis of SUI, besides a thorough clinical examination, the evaluation of bladder neck mobility is performed using complementary diagnostic techniques such as the Q-tip test [6], cystourethrography [7], and imaging of the pelvic floor via transperineal ultrasound (US) [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…UH is commonly underlying stress UI, and has been used as a diagnostic tool, a prognostic factor and a preoperative criterion for anti‐incontinence procedures . There are several methods for UH assessment, but the most commonly used, simple, reliable and inexpensive method has long been the Q‐tip test .…”
Section: Introductionmentioning
confidence: 99%
“…UH is commonly underlying stress UI, and has been used as a diagnostic tool, a prognostic factor and a preoperative criterion for anti-incontinence procedures. [1][2][3][4][5][6][7][8][9] There are several methods for UH assessment, but the most commonly used, simple, reliable and inexpensive method has long been the Q-tip test. 1,3,4,6,10,11 It was introduced in 1971, 12 and the value of 30°above the horizontal has largely been accepted as the cut-off point for UH.…”
Section: Introductionmentioning
confidence: 99%